Usefulness of magnetic resonance imaging to diagnose greater trochanteric-ischial impingement. Issue 4 (4th July 2021) - Hatem, Munif; Canavan, Kathryn E.; Martin, RobRoy L.; Dawkins, Jonathan; Martin, Hal David
Abstract: Extra-articular impingement between the femur and ischium is increasingly recognized as a cause of hip pain. The purpose of this study was to assess the diagnostic parameters for greater trochanteric-ischial impingement (GTI) in magnetic resonance imaging (MRI) studies. Seven patients (seven hips) diagnosed with GTI were retrospectively identified. For each of these seven patients, three controls were matched by gender, height, and weight to create a control group of 21 asymptomatic hips. The same technique and positioning were utilized to acquire the MRIs in the GTI and control groups. The MRI was performed with the lower limbs in a functional position reproducing the midstance phase of the gait cycle. The greater trochanteric-ischial distance was measured in the axial cut showing the shortest distance between the greater trochanter and the ischial tuberosity. The mean greater trochanteric-ischial distance was 26.2 mm in the GTI group and 33.8 mm in the control group ( P  < 0.01). Greater trochanteric-ischial distance ≤28 mm had a sensitivity of 86% and specificity of 86% in identifying GTI. In conclusion, utilizing MRI with functional positioning of the lower limbs, greater trochanter-ischial distance ≤28 mm is helpful to diagnose GTI in women.